Patterns of increases in interleukin‐6 and C‐reactive protein as predictors for white matter injury in preterm infants. Issue 6 (25th November 2014) - Inomata, Kei; Mizobuchi, Masami; Tanaka, Satoshi; Iwatani, Sota; Sakai, Hitomi; Yoshimoto, Seiji; Nakao, Hideto
Abstract Background The aim of this study was to determine whether patterns of increases in serum interleukin‐6 (IL‐6) and C‐reactive protein (CRP) levels at birth were associated with the development of white matter injury (WMI) in preterm infants with a fetal inflammatory response (FIR). Methods One hundred infants who were born at <32 weeks gestation and had funisitis, as determined by histological evidence of FIR, were studied. Infants were divided into four groups according to IL‐6 and CRP levels at birth, with cut‐off values of 200 pg/mL and 0.4 mg/dL, respectively. We compared the incidence of WMI, determined by MRI at term‐equivalent age, among these groups. Results The number of infants in each group was 12, 43, 0, and 45 in the high IL‐6 and high CRP (HH) group, high IL‐6 and low CRP (HL) group, low IL‐6 and high CRP (LH) group, and low IL‐6 and low CRP (LL) group, respectively. The incidence of WMI was significantly higher in the HH group than in the HL group and LL group (83%, 40%, and 34%, respectively). Multiple logistic regression analysis revealed that a combined elevation in IL‐6 and CRP levels was an independent predictor for the development of WMI (odds ratio, 8.3). Conclusion A combined elevation in serum IL‐6 and CRP levels at birth was associated with the development of WMI in preterm infants with FIR.